PH-Responsive magnetic metal–organic framework nanocomposites for selective capture and release of glycoproteins. Issue 2 (14th December 2016) - Yang, Qi; Zhu, Yue; Luo, Bin; Lan, Fang; Wu, Yao; Gu, Zhongwei
Abstract : Novel magnetic metal–organic framework nanocomposites with 1, 4-phenylenebisboronic acid as both an organic ligand and a functional molecule are proposed as a new type of intelligent nanomaterial to selectively capture and release glycoproteins via pH-stimulus-response. Abstract : Novel magnetic metal–organic framework nanocomposites with 1, 4-phenylenebisboronic acid as both an organic ligand and a functional molecule are proposed for the first time as a new type of intelligent nanomaterial to selectively capture and release glycoproteins via pH-stimulus-response, and would be of great potential for use in bio-separation.